2019
DOI: 10.1111/bph.14808
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the hyaluronan matrix enhances metabolic anticancer therapy by dichloroacetate in vitro and in vivo

Abstract: Background and PurposeAerobic glycolysis is a unique feature of tumour cells that entails several advantages for cancer progression such as resistance to apoptosis. The low MW compound, dichloroacetate, is a pyruvate dehydrogenase kinase inhibitor, which restores oxidative phosphorylation and induces apoptosis in a variety of cancer entities. However, its therapeutic effectiveness is limited by resistance mechanisms. This study aimed to examine the role of the anti‐apoptotic hyaluronan (HA) matrix in this cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…The tumor microenvironment is mainly composed of tumor-associated fibroblasts, immune cells, extracellular matrix, various growth factors, inflammatory factors, and tumor cells themselves. Factors inherent to the tumor microenvironment can significantly affect the diagnosis, survival outcome, and treatment sensitivity of tumors (3,5). We further explored the potential molecular mechanism of core genes affecting the progression of ESCA by analyzing the correlation between core genes and tumor immune infiltration in TCGA data sets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tumor microenvironment is mainly composed of tumor-associated fibroblasts, immune cells, extracellular matrix, various growth factors, inflammatory factors, and tumor cells themselves. Factors inherent to the tumor microenvironment can significantly affect the diagnosis, survival outcome, and treatment sensitivity of tumors (3,5). We further explored the potential molecular mechanism of core genes affecting the progression of ESCA by analyzing the correlation between core genes and tumor immune infiltration in TCGA data sets.…”
Section: Resultsmentioning
confidence: 99%
“…China is one of the countries with a high incidence of ESCA. Notably, due to the atypical early symptoms of ESCA, a majority of patients are diagnosed with an advanced stage, often accompanied by distant or lymph node metastases, and the 5-year survival rate is less than 20% (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…The tumor suppressive effect of DCA or Nic combination regimens has been demonstrated in xenografts of different cancer types: DCA/activated natural killer cells/anti-CD20 ( Belkahla et al, 2022 ), DCA/4‐methylumbelliferone ( Twarock et al, 2019 ), DCA/arginase ( Verma et al, 2019 ), DCA/sirtinol (SIRT2 inhibitor) ( Ma et al, 2018 ), DCA/cisplatin ( Woolbright et al, 2018 ), Nic/cisplatin ( Liu et al, 2021 ) and Nic/paclitaxel ( Chen et al, 2017 ). Although either DCA or Nic may exert its tumor suppressive effect in different cancer xenografts, a better anti-cancer effect is usually observed when DCA or Nic is combined with another therapeutic drug.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that FAS inhibitor C75 reduces the activity of B-NHL (124,125). ACLY was proved to be a potential target for anticancer therapy in 2005, and ACLY chemical inhibitor (SB-204990) impaired the proliferation and survival of tumor cells (126)(127)(128). Subsequently, some studies have shown that the expression of ACLY is related to the prognosis of AML (129).…”
Section: Targeting Lipid Metabolismmentioning
confidence: 99%